Konsep Pendidikan Multikultural Dalam Islam - Teuku Amnar Saputra (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2020)
Abstract Indonesia as a multicultural country has the potential to cause conflict in society. Islam as the majority religion must be able to be rahmatan lil alamin for all Indonesian people. This study aims to discuss the ontology and epistemology foundation of multicultural education and how the concept and foundation of Multicultural education in Islam. Multicultural education is an excellent concept applied in the very pluralistic world of education in Indonesia. The purpose of multicultural education itself is to make students pluralistic and able to minimize ethnic, racial, cultural and religious conflicts. The concept of Multicultural education is a concept that is very in accordance with the essence of the teachings of Islam as a religion that is rahmatan lil'alamin and very appreciates the diversity that exists in this world as Firman Allah SWT in Surah Al-Hujurat ayat 13.